"A casual teacher is a gardener": metaphors and identities of casual relief teachers in the Australian primary school context. Issue 3 (4th May 2021) - Uchida, Minami; Cavanagh, Michael; Moloney, Robyn
ABSTRACT: While previous studies have highlighted the significance of metaphors in studying teacher identities and values, little is known about metaphorical representation of teaching as given by casual relief teachers (CRTs). This study examines metaphors from participants who teach or have taught on a casual basis in Australian primary schools. Responses from 39 CRTs were collected using a survey and categorised according to the tripartite model of self, then thematically analysed to discern any commonalities across the metaphors. The major themes generated by CRTs include adopting survival strategies while teaching; feelings of diminished status compared to other staff; and taking on a nurturer role with students. This study adds depth to current research surrounding teacher metaphors and experiences of CRTs.